Structure Design and Flow Field Analysis of a Model Test Box Used to Study Freezing Temperature Field of Seepage Stratum - Renliang Shan; Weijun Liu; Zhe Liu; Zhien Wang (Advances in Materials Science and Engineering)
To meet the research needs of the freezing temperature field under seepage, we investigate and design a seepage-freezing model test box, which can meet the requirements of strength, deformation, dispersed flow, simulated laminar flow, and water sealing performance. Using theoretical analysis and calculation, the pressure design index of the model box was obtained. Based on safety considerations, the model test box was designed with a pressure vessel bearing of 0.05 MPa. The structure of “sink + porous plate” was used inside the box. By flow field analysis, the porous plate can effectively reduce the influence of flow convergence to the orifice on the flow field and achieve the purpose of dispersed-water flow and laminar flow simulation. The composite structure form of “panel + frame beam” was adopted to perform the load-bearing test. Under the pressure of 0.05 MPa, the maximum deformation in the x, y, and z directions was <2.4 mm, and the maximum stress was approximately 248 MPa. The model box could meet the requirements of strength and deformation. Water sealing between the upper cover plate and lower box body was achieved by arranging bolts, iron sheets, and silica gel strips. After testing the processed box, we found that the designed box can fully meet the test requirements. These research results may be used as a reference for the development and design of other seepage-freezing model test boxes.